Enzymes Involved in Antioxidant and Detoxification Processes Present Changes in the Expression Levels of Their Coding Genes under the Stress Caused by the Presence of Antimony in Tomato - Francisco Luis Espinosa-Vellarino; Inmaculada Garrido; Ilda Casimiro; Ana Cláudia Silva; Francisco Espinosa; Alfonso Ortega (Plants, 2024)
Currently, there is an increasing presence of heavy metals and metalloids in soils and water due to anthropogenic activities. However, the biggest problem caused by this increase is the difficulty in recycling these elements and their high permanence in soils. There are plants with great capacity to assimilate these elements or make them less accessible to other organisms. We analyzed the behavior of Solanum lycopersicum L., a crop with great agronomic interest, under the stress caused by antimony (Sb). We evaluated the antioxidant response throughout different exposure times to the metalloid. Our results showed that the enzymes involved in the AsA-GSH cycle show changes in their expression level under the stress caused by Sb but could not find a relationship between the NITROSOGLUTATHIONE REDUCTASE (GSNOR) expression data and nitric oxide (NO) content in tomato roots exposed to Sb. We hypothesize that a better understanding of how these enzymes work could be key to develop more tolerant varieties to this kind of abiotic stress and could explain a greater or lesser phytoremediation capacity. Moreover, we deepened our knowledge about Glutathione S-transferase (GST) and Glutathione Reductase (GR) due to their involvement in the elimination of the xenobiotic component.